Meca: mania de construir - José Marcos Rodrigues Vieira Filho (2019)
Contemporary architecture is obsessed with the unique, the brand new and the spectacular. Architects are perceived as geniuses and feel entitled to express their individuality in their works, with absolute disregard for the collective. Each building is conceived to prevail over the others, to shine brighter than everything around it or better yet, to destroy anything in its path, following a motto of “out with the old, in with the new”. One easy way of accomplishing all of the above at once is to keep building bigger - no wonder this way of thinking has become a staple of the current star system ethos. Nowhere in the world this becomes more readily apparent than in Mecca, Saudi Arabia, where breaking records seems to be the sole, or at least the primary function of the new buildings that keep sprouting around the city. And this being the Holy City of Islam, a religion with an immensely rich heritage and enormous reach around the globe, it makes for a perfect place to ponder past, present and future of architecture worldwide.